Environmental release of and exposure to iron oxide and silver nanoparticles : prospective estimations based on product application scenarios - Wigger, Henning (Springer Vieweg, 2017)
In this thesis a prospective approach was developed to identify and to assess current as well as potentially upcoming product applications with focus on environmental releases and exposures of engineered nanomaterials. The developed product application scenarios were illustrated in case studies on iron oxide and silver nanoparticles. It was shown that despite of prevailing knowledge gaps, reasonable estimations for environmental releases and exposures can be made. This novel approach facilitates the identification of early indicators for precautionary risk management measures and among them benign by design concepts in technology and product development. Contents Product application scenarios for prospective environmental release and exposure assessments Current and future product applications of iron oxide and silver nanoparticles Case study: Clothing textiles with incorporated silver nanoparticles Case study: Magnetic resonance imaging based on iron oxide nanoparticles Target Groups Researchers and students in the field of engineering and natural sciences Practitioners like decision-makers, who are involved in risk assessments particularly in early stages of product and technology development The Author Henning Wigger is a research scientist in the field of nanomaterials and he currently works on the improvement of models for environmental risk assessments of nanomaterials.